Aktivitas Fagositosis Makrofag Peritoneum dan Sel-Sel Penghasil IgA dalam Jaringan Intestinum pada Mencit Yang Diberi Laktoferin Susu Kuda - Nurliyani, Nurliyani (2008)
Lactoferin is an iron-binding glycoprotein, has a very broad range of biological functions relating to the host defence system, e.g as immunomodulator. The aim of this research were to study of horse milk lactoferrin glycan type, and immune responses (phagocytosis activity and IgA producing cells) of mice fed horse milk lactoferin. Horse milk lactoferin was purified on cation exchange chromatography and gel filtration, and glycan type was analyzed with spesific lectin. Female Balb/c mice 6-8 weeks old, fed 0.0 (control); 0.1; 0.5; 1.0 mg/mice/day of horse milk lactoferin orally, in assay period of 28 day. In vitro phagocytosis activity were assayed with latex beads, and IgA producing cells was analyzed with IHC (immunohistochemical) methods. The result showed that molecular weight of horse milk lactoferin was 79.18 kDa, and its glycan type reacted with WGA (wheat germ agglutinine), but not with Con-A (concanavalin A) lectin. The phagocyte cells and IgA producing cells of mice fed horse milk lactoferin were higher than the control mice. In conclusion, horse milk lactoferin had complex type glycan and could stimulate the mice immune responses through the increasing phagocytosis activity of periteal macrophage and IgA producing cells in the intestinal tissue